2002
DOI: 10.1086/339773
|View full text |Cite
|
Sign up to set email alerts
|

AChandraStudy of Sagittarius A East: A Supernova Remnant Regulating the Activity of Our Galactic Center?

Abstract: We report on the X-ray emission from the shell-like, nonthermal radio source Sgr A East (SNR 000.0+00.0), located in the inner few parsecs of the Galaxy based on observations made with the ACIS detector on board the Chandra X-Ray Observatory. This is the first time Sgr A East has been clearly resolved from other complex structures in the region. The X-ray-emitting region is concentrated within the central '2 pc of the larger radio shell. The spectrum shows strong K lines from highly ionized ions of S, Ar, Ca, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
222
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(242 citation statements)
references
References 65 publications
19
222
1
Order By: Relevance
“…Since the non-thermal radio shell still exists, its present velocity must be faster than the sound velocity in the ambient material. According to the authors of [9] this implies that the temperature of the ionised gas halo surrounding Sgr A East is substantially smaller than 70 K which is consistent with the IR observations. The density of the gas halo is about 10 3 cm −3 and it is almost homogenous barring the molecular cloud M-0.02-0.07 where it becomes as large as 10 5 cm −3 [21].…”
Section: Physical Conditions In the Sgr A East Regionsupporting
confidence: 84%
See 2 more Smart Citations
“…Since the non-thermal radio shell still exists, its present velocity must be faster than the sound velocity in the ambient material. According to the authors of [9] this implies that the temperature of the ionised gas halo surrounding Sgr A East is substantially smaller than 70 K which is consistent with the IR observations. The density of the gas halo is about 10 3 cm −3 and it is almost homogenous barring the molecular cloud M-0.02-0.07 where it becomes as large as 10 5 cm −3 [21].…”
Section: Physical Conditions In the Sgr A East Regionsupporting
confidence: 84%
“…The spectacular Chandra [9] X-ray observations, in the energy range 2 − 10 keV, with an angular resolution better than 1", confirmed that Sgr A East is the remnant of a single type II SN with age between 10 4 and 10 5 years. The total luminosity (∼ 8 × 10 34 ergs s −1 in the Chandra energy range) and the spectrum of this source allowed to establish that its progenitor was a main sequence star of mass of 13 − 20 M ⊙ with a metallicity four times larger than that of the Sun.…”
Section: Physical Conditions In the Sgr A East Regionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some authors consider that the molecular ridge actually belongs to M−0.02−0.07 and coincides with the fraction of the cloud that has been swept up and compressed by the Sgr A East forward shock (e.g., Serabyn et al 1992;Maeda et al 2002). In this scenario, the molecular ridge must adhere to Sgr A East and form the eastern part of the gas-and-dust shell surrounding it.…”
Section: The Belt Of Molecular Cloudsmentioning
confidence: 97%
“…Thermal X-ray emission is concentrated in the interior of the remnant, suggesting that Sgr A East is a mixed morphology SNR interacting with the 50 km s −1 molecular cloud (Maeda et al 2002;Park et al 2005). The thermal X-ray emitting plasma has two components, characterized by temperatures of 1 and 6 keV and corresponding electron density of 4.7 and 0.6 cm −3 , respectively.…”
Section: Sgr a East Towermentioning
confidence: 99%